Comparison of urodynamic parameters with respect to neurological levels in post-traumatic spinal cord injury patients - Gaikar, Rohit Ramesh; Gaur, Anil Kumar; More, Sumedh Narayan; Lokhande, Vaibhav Shivram; Khade, Amol Babanrao (International Journal of Research in Medical Sciences, 2020)
Background: Urodynamic evaluation is mandatory in order to correctly assess and classify bladder dysfunction in spinal cord injury (SCI) patients. Study investigated patterns of neurogenic bladder dysfunction in patients with post traumatic spinal cord injury and assessed the relationship of detrusor leak point pressure with compliance, post void residual urine volume and maximum cystometric capacity. Methods: Eighty six patients with neurogenic bladder secondary to traumatic spinal cord injury (SCI) underwent cystometry with electromyography (EMG). T-test was used to compare detrusor leak point pressure (LPP) between complete and incomplete injury groups. Pearson correlation test was used to seek correlation between detrusor LPP and compliance, post void residual volume (PRV) and maximum cystometric capacity (MCC). Results: Mean detrusor LPP in suprasacral complete injury group, suprasacral incomplete injury group and sacral complete injury was 52±21 cm of H2O, 53±18 cm of H2O and 16±9 cm of H2O respectively. No significant difference in detrusor LPP was found between suprasacral complete and incomplete group on t-Test (p= 0.571068). Significant difference in detrusor LPP was found between suprasacral and sacral group (p= 5.71891E-12). Mean compliance in sacral injury group was 24±16 and in suprasacral complete injury group was 5±6. Mean compliance in suprasacral incomplete injury group was 4±2. Pearson correlation showed negative correlation (r = -0.6918934) between detrusor leak point pressure and compliance (p= 1.2744E-13). Negative correlation (r = -0.311409922) was observed between detrusor leak point pressure and post leak/ void residual urine volume (p= 0.003335033) and between detrusor LPP and maximum cystometric capacity (r = -0.31354), (p= 0.003115). Conclusions: Significant difference in urodynamic parameters exists between sacral and suprasacral injury patients. However there is no significant difference in urodynamic parameters between complete and incomplete injury at suprasacral level.